Total Hip Replacement in Three Ponies - A Feasibility Study - Squire, K.R.E.; Fessier, J.F.; Toombs, J. P.; Sickle, D.C. Van; Blevins, W.E.; Clarke, R.B. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
Total hip replacement (THR) using two different human implant designs was performed in three ponies. Pony # 1 sustained a fracture of the ipsilateral femur and was euthanatized 40 hours after implantation of a human selfcentering hip. The same implant, with a modified femoral prosthesis, was used in pony # 2. It luxated initially at 26 hours, was surgically reduced after changing to a smaller diameter acetabular component, and reluxated at day 23 when the pony was euthanatized. A modified femoral component with a press-fit, screw-fixated acetabular prosthesis was inserted in pony # 3. This pony was maintained for 232 days and sustained over 400,000 cycles on the prosthesis by being exercised daily on a mechanical walker. We conclude that THR is feasible in ponies and small horses and would allow this size of animal to be used as a research model for hip replacement in heavy human beings.Total hip replacement (THR) was evaluated in three ponies as a model for studying THR problems in humans and for the management of coxofemo-ral disease in small Equidae. A modified cemented human femoral component, with a press-fit acetabular component, was maintained in one pony for 232 days, sustained over 400,000 cycles, and established the feasibility of THR in this species.
Keywords: Equine; Total hip replacement